Intraspecific variation of insertion/length of stamens in homostylous flowers of a new species and three other species of Borreria: an unusual case in Rubiaceae - Sobrado, Sandra Virginia (Phytotaxa, 2015)
Four species of Borreria subsection Latifoliae (Rubiaceae) present intrafloral variations in the insertion/length of stamens in homostylous flowers. Borreria heteranthera is described and illustrated as new species from the state of Pará, Brazil. The emended descriptions of Borreria hispida, B. semiamplexicaule and B. xanthophylla, with details on stamens morphology and insertion, are provided. The inclusion of B. xanthophylla in the subsection Latifoliae is proposed. Staminal arrangement, pollen grains and seed morphology of the four species are compared. A comparative table with ecological, palynological, and morphological features of each species is provided. In addition, Borreria semiamplexicaule is mentioned as a new record for the state of Mato Grosso, Brazil, and the lectotype of B. hispida is here designated.